The Utilization of Medicinal Plants to Cure Gastrointestinal Disorders by The Dayak Muara Tribe in Kuala Dua Village, Sanggau Regency - Fathul Yusro; Yeni Mariani; Evy Wardenaar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
People use medicinal plants to treat various diseases, one of which is gastric disorders. The study aims to analyze the use of medicinal plants to overcome gastric disorders by the Dayak Muara tribe in Kuala Dua Village, Sanggau Regency. The sampling method was purposive sampling, with the number of respondents was 10% of the total number of households in Kuala Dua Village (91 respondents). The information regarding the medicinal plants used by the Dayak Muara tribe to overcome gastric disorders such as diarrhea, intestinal worms, nausea and vomiting, constipation, gastric, flatulence, and stomachache was collected. Furthermore, data obtained analyzed for the use-value (UV), informant consensus factor (ICF), and fidelity level (FL). The Dayak Muara tribe in Kuala Dua village, Kembayan District, has used 17 species of medicinal plants to overcome gastric disorders. Curcuma longa is the plant with a high use value or UV (0.96), followed by Psidium guajava (0.89) and Zingiber officinale (0.45). The highest value of informant consensus factor or ICF includes the diseases category of diarrhea (0.98), gastric, stomachache, nausea, and vomiting, each of which has an ICF value (0.96), constipation (0.94), intestinal worms and flatulence (0.88). The plants with the highest fidelity level (FL) are Allium sativum, Cymbopogon citratus and Centella asiatica for gastric (100), Areca catechu for constipation (100), Moringa oleifera, and Theobroma cacaoÃÂ (100) for stomachache.